Tempo de reação: relações com tempo sedentário e aptidão fisica de atletas de flag football - COSTA, Thiago Henrique Sousa (2022)
Flag football is a sport derived from American football, sport that has anaerobic characteristics, because its plays take place in seconds. It is perceived that reaction time is a fundamental skill in the course of the game, therefore this work aims to investigate the relations of reaction time with sedentary time and level of physical activity of women flag football athletes. Twelve flag football athletes were evaluated, and evaluations of height, weight, wingspan, and simple reaction time tests (SRT) were evaluated with TReaction® app support, medicine ball pitch and vertical jump using myjump2® app. Statistical analysis was done through the Statistical Package for Social Sciences (SPSS) software with a significance level of p ≤0.05. The analyzed sample presented an average screen time of 195 ± 146.3 min in the three analyzed days. Regarding the mean and median RT value, it did not present statistically significant differences between them and corresponded to 512.83 ± 51.01 and 510.50 ± 48.24, respectively. Were obtained in the physical tests: 4.12 ± 0.34 in the upper limb power test and 29.51 ± 3.24 in the lower limb power test. In the screen time in relation to the mean and median reaction time, a good correlation was found, rho= 0.650 p= 0.016 and rho= 0.719 p= 0.006, respectively. There is a strong correlation between screen time and rho= 0.719 reaction time. As reaction time has involvement in motor response, excessive time in activities considered sedentary can be harmful to performance, even in individuals with a good level of physical activity of the population of individuals considered athletes.